Mechanical behavior of Port Basin Bulkheads Reinforced with novel multi-anchored sheet piles - Jiayun Gao; Xiaojun Li; Yan Zhu; Jie Jiang; Shaojie Tian; Bowen Kang (PLoS ONE, 2026)
To address the critical limitations of conventional parallel double-anchor support systems, including coplanar load imbalance, critical spacing risks, deviations from theoretical designs, and maintenance difficulties, this study proposes an innovative multi-anchored sheet pile reinforcement method. Centrifuge model tests incorporating digital image correlation (DIC) techniques were systematically conducted to investigate the anchoring mechanism of the novel system in port basin bulkhead reinforcement, with a particular emphasis on parameter optimization. The results indicate that the excavation depth predominantly governs the mechanical response of quay walls (sensitivity coefficient 2.3), necessitating phased excavation protocols for deformation control. In contrast, tie-rod horizontal spacing demonstrates low sensitivity (0.018), enabling displacement-controlled dynamic optimization to balance safety and cost-effectiveness. Further, strategic anchor rod installation restructures stress transmission paths, effectively suppressing the shear deformation of shallow soil. The synergistic interaction between prestress application and soil–anchor load transfer mechanisms induces potential migration of the slip surface toward reinforced zones, enhancing stability by 34–41% compared to conventional systems. The developed composite prestressed anchor system achieves a 71.9–77.3% reduction in sheet pile bending moments through stiffness enhancement–stress redistribution coupling effects, establishing a new paradigm for high-performance port infrastructure.